Investigation of selenium and vitamin E deficiency in beef cattle - Dabak, M; Karatas, F; Gul, Y; Kizil, O (Tubitak Scientific & Technological Research Council Turkey, 2002)
Following the successful treatment of a bullock with white muscle disease admitted to the Internal Medicine Clinic of Firat University Faculty of Veterinary Medicine selenium and vitamin E deficiency was ascertained in beef cattles of the same barn Seventeen head of beef cattle randomly selected from the barn suspected of having selenium and vitamin E deficiency and 10 clinically healthy head of beef cattle from a different barn were used All the animals were clinically examined and blood samples were taken for laboratory analysis [serum selenium vitamin E and A Creatine Kinase (CK) and Aspartate Amino Transferase (AST) levels] In addition selenium and vitamin E analysis of the feed were conducted In the experimental group serum selenium vitamin E vitamin A CK and AST levels were found to be 0 058 ppm 1 706 ppm 0 516 ppm 152 64 IU/L and 82 58 IU/L whereas in the control group the levels were found to be 0 269 ppm 2 447 ppm 0 660 ppm 147 5 IU/L and 88 40 IU/L respectively Selenium and vitamin E levels in the experimental group were significantly less (p<0 001) than those in the control group In conclusion although the animals of the experimental group were assessed as being clinically healthy their serum selenium and vitamin E levels were within the marginal range Therefore the animals were considered to be at risk of selenium and vitamin E deficiency.
Besi si?irlarinda selenyum ve E vitamini yetersizli?inin araştirilmasi
Keywords: selenium; vitamin E; deficiency; cattle